2022
DOI: 10.2355/isijinternational.isijint-2021-545
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ce<sub>2</sub>O<sub>3</sub> on the Melt Structure and Properties of CaO–Al<sub>2</sub>O<sub>3</sub>-based Slag

Abstract: The low-reactive tundish flux is urgently required for the smelting of rare-earth steels. The effect of Ce 2 O 3 content on the properties (melting point and viscosity) and structure of CaO-Al 2 O 3 -Ce 2 O 3 -MgO-SiO 2 slag were analyzed in the present investigation. The research results indicated that the polymerized Q Al 4 and Q Al 3 units were modified to Q Al 2 units in aluminate, and the depolymerization of SiO 4 -tetrahedrons from Q Si 1 to Q Si 0 units with Ce 2 O 3 addition increasing from 5 wt% to 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…In addition, the melting temperatures from previous studies, conducted by Zheng et al, [ 30 ] Ou et al, [ 31 ] and Marschall et al, [ 32 ] are also shown in Figure 5. It can be seen that both initial melting temperature and complete melting temperature of these new mold fluxes with waste electrolyte in this study are generally close to those commercial mold flux.…”
Section: Resultsmentioning
confidence: 79%
“…In addition, the melting temperatures from previous studies, conducted by Zheng et al, [ 30 ] Ou et al, [ 31 ] and Marschall et al, [ 32 ] are also shown in Figure 5. It can be seen that both initial melting temperature and complete melting temperature of these new mold fluxes with waste electrolyte in this study are generally close to those commercial mold flux.…”
Section: Resultsmentioning
confidence: 79%
“…It is very important to choose the appropriate melting point of mold flux, which has great influence on the efficiency of the continuous casting process. When the melting point of the mold flux is too large, the liquid flux layer may be too thin, and the steel leakage accident may occur [20][21][22][23] . The melting point of the mold flux can be changed by adjusting the type and content of mineral raw materials.…”
Section: Results and Discussion 31 Effect Of Mineral Raw Materials On...mentioning
confidence: 99%
“…The radius of the diffusing species is listed in Table 4 . [ 17,18,34,35 ] The diffusion coefficient calculated based on Equation (4) is also listed in Table 4.…”
Section: Discussionmentioning
confidence: 99%
“…A similar method was reported in our previous reports. [ 16–18 ] The samples were melted at 1550 °C for 2 h to reach homogenization, and then the samples were quenched with ice water rapidly to obtain the glassy phase. Finally, the premelted slag (about 1.5 g) was mixed with alcohol as the binder in an agate mortar and then pressed into a cube sample (5 mm× 5 mm × 5 mm) under a load of 5 MPa for 5 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation